The Role of University In Improving Competencies of Women Entrepreneurs In Deli Serdang Regency: Bahasa Indonesia - Dalimunthe, Ritha F; Qamariah, Inneke; Nauly, Meutia (Talenta Publisher, 2022)
The objective of this service is to improve the competencies of women entrepreneurs in Deli Serdang Regency so they can sustainably conduct their businesses. This service activity was attended by 25 women entrepreneurs who were also housewives in Deli Serdang Regency. This activity used a qualitative descriptive method by conducting focus group discussions (FGDs), interviews, training, and mentoring. The FGD results show that Universitas Sumatera Utara needs to collaborate with women entrepreneurs in Deli Serdang Regency in increasing entrepreneurial competencies to develop an entrepreneurial spirit. So, these women entrepreneurs can improve their business performance, income, and family welfare. The interview results present that their entrepreneurial reasons cover the hope to give more time to their families and the desire to get more income as well as competencies, namely the ability to take advantage of opportunities and the ability to deal with changes that occur in society. Women entrepreneurs were also given training in the development and marketing of food and beverage products for the export market. The training is meant to increase entrepreneurial competencies, improve product quality, and expand market networks to the global order.